2021
DOI: 10.1096/fj.202100099r
|View full text |Cite
|
Sign up to set email alerts
|

Loss of haspin suppresses cancer cell proliferation by interfering with cell cycle progression at multiple stages

Abstract: Our recent studies have shown that haspin, a protein kinase imperative for mitosis, is engaged in the interphase progression of HeLa and U2OS cancer cells. In this investigation, we employed the Fucci reporter system and time-lapse imaging to examine the impact of haspin gene silencing on cell cycle progressions at a single-cell level. We found that the loss of haspin induced multiple cell cycle defects. Specifically, the S/G2 duration was greatly prolonged by haspin gene depletion or inhibition in synchronous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…To validate these findings, we employed Haspin siRNA in 293T cells (Figure S2). Similarly, Haspin knockdown resulted in decreased H3T3ph levels without affecting H3S10ph (Figure S2b–d), which aligns with previous reports (Dai et al, 2005; Wang et al, 2021). Additionally, H3.3S31ph levels significantly decreased in Haspin siRNA treated‐293T cells, further supporting the role of Haspin in H3.3S31 phosphorylation (Figure S2e–g).…”
Section: Resultssupporting
confidence: 92%
“…To validate these findings, we employed Haspin siRNA in 293T cells (Figure S2). Similarly, Haspin knockdown resulted in decreased H3T3ph levels without affecting H3S10ph (Figure S2b–d), which aligns with previous reports (Dai et al, 2005; Wang et al, 2021). Additionally, H3.3S31ph levels significantly decreased in Haspin siRNA treated‐293T cells, further supporting the role of Haspin in H3.3S31 phosphorylation (Figure S2e–g).…”
Section: Resultssupporting
confidence: 92%
“…Importantly, several studies have demonstrated that the expression of Haspin is significant in several cancer cells in addition to normal proliferating somatic cells [ 60 ]. Specifically, the overexpression of Haspin in breast [ 61 ], pancreas [ 62 ], skin [ 63 , 64 ], lung [ 63 , 64 ], bone [ 63 , 64 ], prostate [ 62 ], and bladder [ 65 ] was reported. By interfering with normal mitotic progression, Haspin knockdown or small molecule inhibition could stop the proliferation of cancer cells and trigger apoptosis [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another haspin inhibitor, CX-6258 also impaired proliferation and generated the formation of micronuclei in melanoma cell lines [ 125 ]. In some cell lines, co-depletion of either p21 or p53 rescues the impairment in cell cycle progression caused haspin depletion [ 148 ]. Moreover, haspin elimination by CRISPR sensitizes tumor cells to VX680, an Aurora kinase B inhibitor in head and neck squamous cell carcinomas (HNSCC) and non-small cell lung cancer (NSCLC) cell lines [ 149 ].…”
Section: Targeting Nuclear Kinases Associated With Chromatin Remodeli...mentioning
confidence: 99%